Woodsong: three-times newbery honor author - Paulsen, Gary (SCHOLASTIC INC., 1991)
Gary Paulsen, three-time Newbery Honor author, is no stranger to adventure. He has flown off the back of a dogsled and down a frozen waterfall to near disaster, and waited for a giant bear to seal his fate with one slap of a claw. He has led a team of sled dogs toward the Alaskan Mountain Range in an Iditarod-the grueling, 1180-mile dog sled race-hallucinating from lack of sleep, but determined to finish. Here, in vivid detail, Paulsen recounts several of the remarkable experiences that shaped his life and inspired his award-winning writing.